2023
DOI: 10.1001/jamanetworkopen.2023.3404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Version 4 of the Emergency Severity Index in US Emergency Departments for the Rate of Mistriage

Abstract: ImportanceAccurate emergency department (ED) triage is essential to prioritize the most critically ill patients and distribute resources appropriately. The most used triage system in the US is the Emergency Severity Index (ESI).ObjectivesTo derive and validate an algorithm to assess the rate of mistriage and to identify characteristics associated with mistriage.Design, Setting, and ParticipantsThis retrospective cohort study created operational definitions for each ESI level that use ED visit electronic health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…Adding triage nurse clinical assessments to the prediction model led to a similar or higher AUC for predicting hospitalization compared to results reported in earlier models. 4 In this study, we found that deep learning methods could achieve high sensitivity at lower hospital admission risk thresholds (>90% in all models at 10% admission threshold) and high specificity at higher hospital risk thresholds (>95% in each model at 30% and 50% risk thresholds).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Adding triage nurse clinical assessments to the prediction model led to a similar or higher AUC for predicting hospitalization compared to results reported in earlier models. 4 In this study, we found that deep learning methods could achieve high sensitivity at lower hospital admission risk thresholds (>90% in all models at 10% admission threshold) and high specificity at higher hospital risk thresholds (>95% in each model at 30% and 50% risk thresholds).…”
Section: Discussionmentioning
confidence: 53%
“…A large multicenter study estimated the ESI to be accurate in <50% of high acuity cases, with no difference in overall accuracy according to nurse experience 2 . Using novel measures to define under‐ and overtriage for each ESI level, we recently reported that mistriage with ESI occurs in over 30% of encounters, with overtriage much more common than under triage 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have documented major disparities in the assignment of ESI triage scores to ED patients according to their race and ethnicity . Specifically, Black and Hispanic patients tend to be assigned lower-acuity triage scores than were White patients, even with identical chief symptoms, such as abdominal pain .…”
Section: Introductionmentioning
confidence: 99%